The Effect of Auditor's Competency and Ethics on Audit Quality in Public Accounting Firm in South Jakarta - Shofia Asry (Kusuma Negara Business School, 2021)
This study aims to determine: (1) the effect of auditor competence on audit quality at KAP (Public Accounting Firm) in South Jakarta. (2) The influence of auditor ethics on audit quality at KAP in South Jakarta. The population of this study are auditors who work at a Public Accounting Firm in South Jakarta. The sample used in this study were 74 respondents. The data in this study were obtained primarily through a questionnaire (questionnaire). The sampling technique used purposive sample. The questionnaire in the Validity Test and Reliability Test, the result is that there are 41 valid and reliable statements with 70 respondents. The classical assumption test used is the normality test, linearity test, multicollinearity test, and heteroscedasticity test. The result is that all variables meet the criteria for the classical assumption test. The results of this study indicate that (1) There is a positive and significant effect of competence on audit quality at KAP in South Jakarta. This is indicated by the value of t arithmetic 4.058 > t table 1.996, the value of Sig. for the influence of Auditor Competency of 0.000 <0.05, the coefficient of the influence of Competence (X1) on Audit Quality (Y) is 0.288. (2) There is a positive and significant effect of auditor ethics on audit quality at KAP in South Jakarta. This is indicated by the t arithmetic value of 3.965 > t table of 1.996, the value of Sig. for the effect of Auditor Ethics (X2) on Audit Quality (Y) is 0.000 < 0.05, the coefficient value of the influence of Auditor Ethics on Audit Quality is 0.327. (3) There is a positive and significant effect jointly on the competence and ethics of auditors on audit quality at KAP in South Jakarta. This is evidenced by the calculated F value of 13.292 which means it is greater than F table 3.13 and the Sig value. (Significance) of 0.000 > (less than) 0.05. The value of the coefficient of determination is known. The R value is ,697, if it is presented as 69.7%, it shows the magnitude of the significant influence value, and the remaining 30.3% is influenced by other variables outside of this study.